Ethnopharmacological application of chamomile (Matricaria chamomilla L.) in the Pirot County of Southeastern Serbia - Marković, Marija; Pljevljakušić, Dejan; Kojičić, Ksenija; Cupara, Snežana (Archives of Pharmacy, 2020)
Chamomile (Matricaria chamomilla L.) is a herbaceous plant from family Astereaceae, that has a long history of use in traditional medicine. The first written report of chamomile was found in Ancient Egypt: crushed chamomile flower-heads were used to relieve skin inflammation, prevent dermatitis, and in cosmetic preparations. The subject of this study was to examine the ethnopharmacological application of chamomile in the Pirot County of Serbia. The study was conducted in the form of a population survey on the population of four municipalities: Pirot, Babušnica, Bela Palanka, and Dimitrovgrad. This study shows that chamomile has been one of the ten best known medicinal plant species in Pirot County. The most common way of the application was a herbal tea for oral use against cold, stomach diseases, throat infection, and mild sedation. Externally, in the form of compresses, it has been used against eye swelling, skin inflammation, and infections, while the oily form was used in the treatment of wounds and burns.